Lasing Emission from Plasmonic Nanodome Arrays. Issue 5 (11th January 2016) - Wu, Hsin‐Yu; Liu, Longju; Lu, Meng; Cunningham, Brian T.
Abstract : Plasmonic nano‐dome arrays (PNDA) have been previously studied as chemical and biological sensors. The present study reports large‐area plasmonic lasing from the PNDA structures with liquid‐phase gain materials to provide optical gain. The PDNA structure consists of a 2D array of nanoposts, fabricated inexpensively using a nanoreplica molding process, with silicon dioxide and gold thin‐film coatings to produce the dome‐shaped surface profile. Covered with a dye‐doped solution, the PDNA structures can generate lasing emission when they are optically pumped above the lasing threshold. The lasing emission is enabled by energy coupling from the photoexcited dye molecules to the hybridized plasmon mode supported by the PDNA oscillator. Two PDNA lasers with array periods of 400 and 450 nm are fabricated and characterized. Plasmonic resonant modes of the PDNA lasers are numerically studied to illustrate the underlying lasing mechanism. The emission characteristics, including lasing wavelength, linewidth, threshold, beam divergence, and radiation angle, are presented in the paper. The PNDA laser represents a new path for plasmonic lasing in the near‐infrared region with potential applications that include integrated photonic circuits, optical communications, and high‐performance biosensors. Abstract : A new feedback mechanism to achieve nano‐lasing is demonstrated. Energy coupling from photoexcited liquid dye molecules to the hybridized plasmon mode supported by a plasmonic nano‐dome array (PNDA) structure enables room‐temperature lasing emission at a low threshold. The unique off‐normal lasing phenomenon in the PNDA lasers provides useful applications which cannot be implemented by other plasmonic lasers.